A large-scale benchmark for network inference from single-cell perturbation data - Mathieu Chevalley; Yusuf H. Roohani; Arash Mehrjou; Jure Leskovec; Patrick Schwab (Communications Biology)
Abstract Mapping biological mechanisms in cellular systems is a fundamental step in early-stage drug discovery that serves to generate hypotheses on what disease-relevant molecular targets may effectively be modulated by pharmacological interventions. With the advent of high-throughput methods for measuring single-cell gene expression under genetic perturbations, we now have effective means for generating evidence for causal gene-gene interactions at scale. However, evaluating the performance of network inference methods in real-world environments is challenging due to the lack of ground-truth knowledge. Moreover, traditional evaluations conducted on synthetic datasets do not reflect the performance in real-world systems. We thus introduce CausalBench, a benchmark suite revolutionizing network inference evaluation with real-world, large-scale single-cell perturbation data. CausalBench, distinct from existing benchmarks, offers biologically-motivated metrics and distribution-based interventional measures, providing a more realistic evaluation of network inference methods. An initial systematic evaluation of state-of-the-art causal inference methods using our CausalBench suite highlights how poor scalability of existing methods limits performance. Moreover, methods that use interventional information do not outperform those that only use observational data, contrary to what is observed on synthetic benchmarks. CausalBench subsequently enables the development of numerous promising methods through a community challenge, thus demonstrating its potential as a transformative tool in the field of computational biology, bridging the gap between theoretical innovation and practical application in drug discovery and disease understanding. Thus, CausalBench opens new avenues for method developers in causal network inference research, and provides to practitioners a principled and reliable way to track progress in network methods for real-world interventional data.